PROFESSOR K. KURAMBAEV'S LITERARY RELATIONS CONTRIBUTION TO PROGRESS - Ametova, Muxabbat Orazimbetovna (SCIENCE and SOCIETY, 2026)
The article discusses the creative path of the renowned Uzbek scholar K.Quramboyev, his role in the literary relations of the Turkic peoples, and the significance of his sciyentific works.
Keywords: literary communication; literary translation; monograph; literary school; literature of the Turkic peoples